2008
DOI: 10.1021/cg8009496
|View full text |Cite
|
Sign up to set email alerts
|

Exploring an Anti-Crystal Engineering Approach to the Preparation of Pharmaceutically Active Ionic Liquids

Abstract: A series of salts, some of which are ionic liquids, are prepared from cations and anions drawn from Active Pharmaceutical Ingredients (APIs) and Generally Recognized As Safe (GRAS) materials. Using the solid-state structures of the crystalline salts as a basis, an anti-crystal engineering approach to the preparation of “Active Ionic Liquids” (AILs) is explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
111
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 25 publications
(27 reference statements)
0
111
0
1
Order By: Relevance
“…The realization that task-specific ILs can be created via simple and systematic chemical modifications of the constituent ions takes these systems beyond the promise of designer solvents to highly useful systems for diverse applications including drug delivery and as active pharmaceutical ingredients, [1][2][3] solvents for green processing of otherwise insoluble biomolecules such as cellulose, 4,5 highly energetic materials, 1 and novel electrolytes for energy applications such as batteries, fuel cells, and solar photoelectrochemical cells. [6][7][8][9] Plechkova and Seddon 10 estimated that there may be in excess of 10 6 possible ILs if all currently known IL cations and anions were to be paired, and as many as 10 18 if all ternary systems were to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The realization that task-specific ILs can be created via simple and systematic chemical modifications of the constituent ions takes these systems beyond the promise of designer solvents to highly useful systems for diverse applications including drug delivery and as active pharmaceutical ingredients, [1][2][3] solvents for green processing of otherwise insoluble biomolecules such as cellulose, 4,5 highly energetic materials, 1 and novel electrolytes for energy applications such as batteries, fuel cells, and solar photoelectrochemical cells. [6][7][8][9] Plechkova and Seddon 10 estimated that there may be in excess of 10 6 possible ILs if all currently known IL cations and anions were to be paired, and as many as 10 18 if all ternary systems were to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the IL propantheline acesulfamate contains the active cation from the API propantheline bromide (an antimuscurinic used to treat a number of conditions such as excessive sweating, cramps, spasms of the stomach, etc.) with acesulfamate, a known artificial sweetener and a pharmaceutical additive (Dean et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bica and co-workers studied ILs based on analgesic, anti-pyretic and anti-inflammatory compounds (acetylsalicylic and salicylic acids) . Hough et al (Hough-Troutman et al, 2009) and MacFarlane et al (Dean et al, 2009) reported API-ILs containing various active cations/anions, while Cybulski and co-workers (Cybulski et al, 2011) prepared ILs based on antiseptic/disinfectant cations and enzyme/amino acids anions, which were found to be very effective against bacteria and fungi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering work of Wilkes and Zaworotko [6] (yes the same one) had set the stage for air stable room temperature liquid salts to find numerous applications and Seddon's use of these caught the imagination of many scientists and engineers. [7] Since the mid 1990s an excess of 15000 papers have appeared using the term 'Ionic Liquids' and only a few have noted the true relationship between this field and Crystal Engineering (one of those by Doug MacFarlane [8] ). Nonetheless, they are quite related.…”
mentioning
confidence: 99%